Urbach energy parameter of flash evaporated amorphous gallium arsenide films - Silva, José Humberto Dias da [UNESP] (2002)
The dependence of the optical absorption edge on the deposition crucible temperature is used to investigate the electronic states in As-rich a-GaAs flash evaporated films. The Urbach energy parameter, determined from photothermal deflection spectroscopy (PDS), presents large correlated variations with crucible temperature. The optical and electrical results are consistent with the As under coordinated sites being the more important defect in the material. © 2002 Elsevier Science B.V. All rights reserved.